Hardiness Shields Against Depression in Iraqi Dialysis Patients: Ketahanan Melawan Depresi pada Pasien Dialisis di Irak - Mustafa A. Abid; Tahseen R. Mohammed (Academia Open, 2024)
Background: Renal dialysis patients face numerous challenges throughout treatment and experience significant psychological pressures, including depression. The positive impact of psychological hardiness on mental health is notable and can lead to improved outcomes for individuals with depression. Specific Background: Depression is prevalent among renal failure patients, often going unrecognized and adversely affecting daily routines, social interactions, and overall well-being, potentially leading to higher mortality rates. Knowledge Gap: While the relationship between psychological hardiness and depression in renal failure patients has been suggested, comprehensive data quantifying this relationship is lacking. Aims: This study aims to determine the prevalence of depression symptoms and their correlation with psychological hardiness in renal failure patients undergoing hemodialysis. Results: Conducted as a descriptive correlational study from December 2023 to May 2024, 200 patients from Baghdad hospitals participated. The average age was 48.21 years, with 53% being male. Depression symptoms were reported at minimal (29.5%) and moderate (25.5%) levels, with an overall mean depression score indicating a moderate level (20.335±10.783). Psychological hardiness was moderate in 52.5% of patients. A significant negative correlation was found between psychological hardiness and depression symptoms (p-value = 0.001). Novelty: This study highlights the moderate levels of both psychological hardiness and depression symptoms among renal failure patients and establishes a significant inverse relationship between the two variables, suggesting that higher psychological hardiness is associated with lower depression symptoms. Implications: The findings suggest the need for community institutions to provide comprehensive support, boost self-confidence, and enhance life satisfaction for renal failure patients. Hiighligt: Moderate depression and psychological hardiness levels in renal failure patients. Significant negative correlation between psychological hardiness and depression symptoms. Support and counseling programs recommended to enhance mental health and resilience Keyword: Renal dialysis, depression, psychological hardiness, hemodialysis, mental health